2016
DOI: 10.1590/0104-1428.2066
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and applications of polystyrene-block-poly(N-vinyl-2-pyrrolidone) copolymers

Abstract: SbstractThis work describes the synthesis and applications of amphiphilic polystyrene-block-poly(N-vinyl-2-pyrrolidone) (PS-b-PVP) copolymers as a silver and silica nanoparticle surface modification agent. The synthesis of PS-b-PVP was carried out using controlled/living radical polymerization techniques. The synthesis of the block copolymers was confirmed by gel permeation chromatography and hydrogen nuclear magnetic resonance, presenting a polydispersity index of around 1.4 and number average molecular weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
(74 reference statements)
0
6
0
1
Order By: Relevance
“…In 2007, Lu et al reported the application of atom transfer radical polymerization (ATRP) in producing PVP of molecular weight around 8900 with PDI of 1.2–1.38 [ 32 , 33 ]. Advances in the procedures of controlled radical polymerization (CRP)/LRP [ [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ], ATRPf [ 43 ], and reversible addition-fragmentation transfer radical polymerization (RAFT) [ 44 , 45 ] have created new avenues for better control on the synthesis of PVP and its derivatives.…”
Section: Preparation Methods Of Pvp and Its Derivativesmentioning
confidence: 99%
“…In 2007, Lu et al reported the application of atom transfer radical polymerization (ATRP) in producing PVP of molecular weight around 8900 with PDI of 1.2–1.38 [ 32 , 33 ]. Advances in the procedures of controlled radical polymerization (CRP)/LRP [ [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] ], ATRPf [ 43 ], and reversible addition-fragmentation transfer radical polymerization (RAFT) [ 44 , 45 ] have created new avenues for better control on the synthesis of PVP and its derivatives.…”
Section: Preparation Methods Of Pvp and Its Derivativesmentioning
confidence: 99%
“…All polymers showed narrow dispersity, below 1.2 (see Table 1) as reported in literature for PS and derivatives synthesized by Nitroxide-Mediated Polymerization. 41–43 This showed that the initiation of vinyl benzyl chloride by PS-SG1 was controlled and the narrow dispersity was kept even after the click reaction. The molar mass of PS macro-initiator calculated from SEC analysis using PS calibration was equal to 32 000 g mol −1 .…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, proton nuclear magnetic resonance ( 1 H NMR) spectroscopy analyses of the re-solubilized washed fibers were performed. The NMR spectra and peak attributions 35 are shown in Figure 7 . The ratio of PS to PVP after washing was calculated from the proton intensities of PS and PVP and used to determine the percent of PVP removed ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%